Antibiotic use in acute respiratory infections in under-fives in Uganda: findings and implications. Issue 9 (1st September 2016) - Kibuule, Dan; Kagoya, Harriet Rachel; Godman, Brian
ABSTRACT: Background : Self-medication with antibiotics among households is common in Uganda. However, there are limited studies evaluating self-purchasing of antibiotics for acute respiratory infections (ARI) in the under-fives. Consequently, the objective of this study was to evaluate patterns of household self-medication with antibiotics in ARI among under-fives in Kampala. Methods : Descriptive cross-sectional observational design. Care takers at households were selected from five divisions of Kampala using the WHO 30-cluster method and interviewed using a standardized questionnaire in June - July 2011. Results : Out of the 200 households, most ARI cases 107 (53.5%; p = 0.322) were inappropriately managed. The prevalence of antibiotic use in ARI was 43% ( p < 0.001). Amoxicillin (31.4%) and cotrimoxazole (30%) were the most self-medicated antibiotics. Antibiotics use was associated with pneumonia symptoms and access to antibiotics. Conclusions : Household use of antibiotics in ARIs among under-fives is suboptimal. There is an urgent need for guidelines on awareness to reduce self-medication of ARIs in Uganda.